La festividad de la Mamacha del Carmen en Paucartambo como espacio de resistencia ante la mirada secularizadora del mundo - Revilla Valdivia, Camila (2026)
This essay examines how the festivity of the Virgin of Carmen in Paucartambo emerges as a space of resistance against secularizing perspectives that have established antithetical boundaries between the religious and the political, the public and the private. It argues that this celebration reconfigures such premises by intervening in the public sphere, inscribing its own political subjectivity within a collective narrative, and adapting to modernization processes that, rather than dissolving its socio-spiritual identity, ultimately strengthen it. Within this framework, the study seeks to identify the main propositions of the secularization paradigm in order to develop a well-founded critique from the standpoint of popular religion, understood through a situated interpretive approach focused on the lived experiences of participants and the internal dynamics of festive sequences within patronal celebrations. To this end, a literature review is conducted to contextualize the study, clarify key concepts—secularization and popular religion—and provide theoretical grounding for the findings. The discussion then turns to the contemporary context of Paucartambo, integrating visual records as complementary interpretive resources aimed at more deeply representing the tensions and meanings inherent in religious experience. Ultimately, this essay concludes that the symbolic reaffirmation of Paucartambo’s socio-spiritual identity subverts epistemic hierarchies and affirms the persistence of worldviews in which the sacred and the political are interwoven in ways that the secular paradigm fails to fully grasp.